Molybdenum Foliar Fertilization Improves Photosynthetic Metabolism and Grain Yields of Field-Grown Soybean and Maize - Oliveira, Sirlene Lopes; Crusciol, Carlos Alexandre Costa; Rodrigues, Vitor Alves; Galeriani, Tatiani Mayara; Portugal, José Roberto; Bossolani, João William; Moretti, Luiz Gustavo; Calonego, Juliano Carlos; Cantarella, Heitor (Frontiers in Plant Science, 2022)
Foliar fertilization has been used as a supplemental strategy to plant nutrition especially in crops with high yield potential. Applying nutrients in small doses stimulates photosynthesis and increases yield performance. The aim of this study was to evaluate the efficiency of foliar application of molybdenum (Mo) to soybean and maize. The treatments consisted of the presence (+Mo) and absence (-Mo) of supplementation. Plant nutritional status, nitrate reductase (NR) activity, gas exchange parameters, photosynthetic enzyme activity (Rubisco in soybean and maize and PEPcase in maize), total soluble sugar concentration, leaf protein content, shoot dry matter, shoot nitrogen accumulated, number of grains per plant, mass of 100 grains and grain yield were evaluated. For soybean and maize, application of Mo increased leaf NR activity, nitrogen and protein content, Rubisco activity, net photosynthesis, and grain yield. These results indicate that foliar fertilization with Mo can efficiently enhance nitrogen metabolism and the plant's response to carbon fixation, resulting in improved crop yields.